Yhwh's Defense of Moses in Numbers 12 - Sweeney, Marvin A. (Hebrew studies, 2025)
The account of Yhwh's support of Moses in Numbers 12 raises some key questions concerning Moses's status as Yhwh's spokesman in the Wilderness narratives. The narrative states that Moses had taken a Cushite wife and that his Levite siblings, Miriam and Aaron, objected to his intermarriage. Although some interpreters have argued that Moses had taken a new wife after having allegedly divorced Zipporah, such a contention does not stand up to scrutiny, insofar as Zipporah bat Jethro, as the daughter of a Midianite priest, would have been considered a Cushite in ancient Israel and Judah. The key issue in the narrative is Zipporah's non-Israelite identity, particularly because Moses is a Levite who would be forbidden to marry a foreign woman as stipulated in Lev 21.10-15, esp. vv. 14-15. Yhwh's support of Moses in this instance is surprising. But consideration of several intertextual references indicate that Zipporah is a suitable mate for Moses. Consideration of Exodus 2 and Exodus 18 indicate that no divorce took place between Moses and Zipporah, so that she is indeed still Moses's wife. Examination of references in Song 1:5 and Hab 3:7 indicate that Zipporah is indeed a Cushite due to her dark skin. Despite warnings against the marriage of foreign women in Exod 23:27-33; 34:10-16; and Deut 7:1-8, and a polemic against Midianite women in Num 25:6-16, the account of Zipporah's circumcision of her son, Gershom, in Exod 4:24-26 demonstrates that she is a righteous Gentile that makes her a suitable mate for Moses in the eyes of Yhwh.